Adhesive Strength of Hexadecane on Different Iron Compounds: an MD Approach - Ta, Dinh Hien (Journal of Technical Education Science, 2022)
The lubricity of alkane is a research target for numerous tribological applications in either industrial area or fundamental scientific studies. In the current work, a comparative investigation using a classical molecular dynamics (MD) method is carried out to investigate the effect of pure iron and its oxide surfaces on structural properties, adsorption ability of hexadecane (C16H34). A reliable force field (FF) of condensed-phase optimized molecular potentials for atomistic simulation studies (COMPASS) is employed to describe the intra- and intermolecular interactions for hexadecane and its interaction with iron oxide surfaces, while the interaction between hexadecane and pure iron is derived from an ab initio result. Regarding the surfaces, the pure iron surfaces are considered using embedded-atom method/Finnis-Sinclair potential (EAM/FS), while the iron oxide surfaces are constructed using the traditional Buckingham force field. The results reveal that hexadecane shows preferential adsorption on iron oxide surfaces compared to pure iron.